2021
DOI: 10.1097/mat.0000000000001379
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Assist Device Implantation in Patients with Preoperative Severe Mitral Regurgitation

Abstract: We examined cardiac features associated with residual mitral regurgitation (MR) following continuous-flow left ventricular assist device (cfLVAD) implant. From 2003 to 2017, 134 patients with severe MR underwent cfVLAD implant without mitral valve (MV) intervention. Echocardiographic (echo) assessment occurred pre-cfLVAD, early post-cfLVAD, and at last available echo. Ventricular and atrial volumes were calculated from established formulas and normalized to be predicted. Cluster analysis based on preoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Building upon findings by previous groups on predictor of residual SMR, we employed a non-hypothesis driven statistical phenotyping of cardiac chamber dimensions. This revealed the correlations between pre-cfLVAD chamber size to MV tenting, early and late post-cfLVAD MR resolution and the occurrence of RV failure ( 30 ). Interestingly, LV and left atrial (LA) sizes greater than 3 times the normalized dimensions had twice the risk of having residual SMR at last follow up compared to those less than 3 times the normal size (50–55% vs. 25% respectively).…”
Section: Resolution Of Mitral Regurgitation In the Left Ventricular A...mentioning
confidence: 98%
See 4 more Smart Citations
“…Building upon findings by previous groups on predictor of residual SMR, we employed a non-hypothesis driven statistical phenotyping of cardiac chamber dimensions. This revealed the correlations between pre-cfLVAD chamber size to MV tenting, early and late post-cfLVAD MR resolution and the occurrence of RV failure ( 30 ). Interestingly, LV and left atrial (LA) sizes greater than 3 times the normalized dimensions had twice the risk of having residual SMR at last follow up compared to those less than 3 times the normal size (50–55% vs. 25% respectively).…”
Section: Resolution Of Mitral Regurgitation In the Left Ventricular A...mentioning
confidence: 98%
“…These patients were two times more likely to have severe RV dysfunction and over three times the rate of manifesting the clinical symptoms of late RV failure. Late RV failure also highly correlated with lower survival ( P = 0.006) ( 30 ). Kassis et al reported similar findings where postoperative LVEDD and RV dimensions was larger in patients with significant residual MR and this was associated with worse RV function by quantitative parameters ( 20 ).…”
Section: Residual Mitral Regurgitation and Right Ventricular Failurementioning
confidence: 99%
See 3 more Smart Citations